Molecular neuro-oncology in clinical practice: a new horizon - Weller, Michael; Pfister, Stefan; Wick, Wolfgang; Hegi, Monika E; Reifenberger, Guido; Stupp, Roger (The lancet. Oncology, 2013)
Primary brain tumours are heterogeneous in histology, genetics, and outcome. Although WHO's classification of tumours of the CNS has greatly helped to standardise diagnostic criteria worldwide, it does not consider the substantial progress that has been made in the molecular classification of many brain tumours. Recent practice-changing clinical trials have defined a role for routine assessment of MGMT promoter methylation in glioblastomas in elderly people, and 1p and 19q codeletions in anaplastic oligodendroglial tumours. Moreover, large-scale molecular profiling approaches have identified new mutations in gliomas, affecting IDH1, IDH2, H3F3, ATRX, and CIC, which has allowed subclassification of gliomas into distinct molecular subgroups with characteristic features of age, localisation, and outcome. However, these molecular approaches cannot yet predict patients' benefit from therapeutic interventions. Similarly, transcriptome-based classification of medulloblastoma has delineated four variants that might now be candidate diseases in which to explore novel targeted agents.
Gesehen am 02.11.2021